2013
DOI: 10.3122/jabfm.2013.06.130108
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Skills and Practice from a Web-Based Skin Cancer Course for Primary Care Providers

Abstract: Background: Melanoma incidence and mortality is a growing concern. Better recognition and management of skin cancer by primary care providers (PCPs) could help, but studies suggest they would benefit from additional education. Effective educational programs are needed.Methods: We developed and conducted a voluntary before-and-after evaluation of a 1-to 2-hour interactive, web-based course in skin cancer detection for practicing, board-certified PCPs (http:// www.skinsight.com/info/for_professionals/dermatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 19 publications
3
81
0
Order By: Relevance
“…Providers generally felt more comfortable with deciding what lesions were appropriate to be referred to dermatology, reinforcing the quantitative findings of improved confidence and attitude towards skin cancer identification [7]. Many participants desired more time with the curriculum and a few suggested having an expert-guided (dermatologist) curriculum so as to be able to ask questions and receive direct feedback.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Providers generally felt more comfortable with deciding what lesions were appropriate to be referred to dermatology, reinforcing the quantitative findings of improved confidence and attitude towards skin cancer identification [7]. Many participants desired more time with the curriculum and a few suggested having an expert-guided (dermatologist) curriculum so as to be able to ask questions and receive direct feedback.…”
Section: Resultsmentioning
confidence: 83%
“…Fifty-four percent were women and participants were diverse in race/ethnicity. Complete demographics have been previously published [7]. The 4 domains from feedback sessions are presented below, and representative quotations are presented in Tables 1–4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Related to another cancer-melanoma-Roetzheim et al 2 showed that visiting a family physician compared with only a dermatologist before the diagnosis of melanoma was associated with a diagnosis of more thin melanomas and possibly a lower rate of mortality. To improve the accuracy of detection of skin cancers, Eide et al 3 tested an intriguing intervention using a readily available, 1-to 2-hour, interactive web-based course. In addition to evaluations after the course, this study considered referrals to dermatology before and after the course and diagnoses after the course.…”
mentioning
confidence: 99%